Polarographic Studies on interaction of 2-Aminoquinoxaline with Cd(II) in Alkanols, Formamide, Dimethyl Formamide and Dimethyl Sulphoxide Solvent Mixture - Pratihar, P.L. (Asian Journal of Chemistry, 2010)
The present study deals with the determination of composition and stability constants of Cd(II)-2-aminoquinoxaline complexes in 25, 50 and 75% (by volume) aqueous methanol solution. In each case, the single well defined reduction wave appeared. The plots of id vs., confirmed that the reduction was of diffusion control. The reversible nature of the electrode reaction was evident from the slopes of the Ed.e vs. log i/id–i curves which were of the order of 31 ± 2 m V. The indication of the formation of Cd(II) complexes with 2-aminoquinoxaline was provided by the shift in the E1/2 values to more negative potentials ana decrease in the diffusion currents with the increasing concentration of the ligand. The complexes formed by 2-aminoquinoxaline are very weak which confirm the validity of Deford and Hume's method to calculate the consecutive formation constants of very weak complexes, which may not be detected by other techniques. The low stabilities of the complexes of 2-aminoquinoxaline may be due to the less tendency of the amino-group to donate electrons because of delocalisation of electrons in the heterocyclic ring. Thus it is obvious that the nature and concentration of the solvent not only affects the stability, but the composition of complexes formed also.